Jews and Christians in the Roman World from historical method to cases - Mason, Steve 1957- (Leiden Boston Brill, 2023)
"Roman Judaea, Christian origins, and Roman-Judaean-Christian relations are flourishing fields of endless fascination. Amid the flurry of new research, however, which uses ever new methods in the humanities and social sciences, basic questions about what happened and how people then understood events are easily obscured. This book argues that a simple but consistent historical method can throw new light - and challenge entrenched views - on such familiar topics as Roman provincial governance, the Jewish War, Flavian politics, Judaea after King Herod, Jewish and Christian historiography, Pharisees and Essenes, John the Baptist, the apostle Paul, and Luke-Acts"--
Includes bibliographical references and index
English
Keywords: Christianity -- Rome -- History; Christianity and other religions -- Judaism; Judaism -- Historiography; Judaism -- Rome -- History; Judaism -- Relations -- Christianity; Jews -- History -- Historiography; Judaism -- Relations -- Christianity; Jews -- Historiography; Jews -- History -- Historiography; Rome -- Religion